2016
DOI: 10.1007/s10620-016-4208-0
|View full text |Cite
|
Sign up to set email alerts
|

Good Clinical Outcomes in Budd–Chiari Syndrome with Hepatic Vein Occlusion

Abstract: HV angioplasty and TIPS yield excellent long-term outcomes in patients with HV occlusive BCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 27 publications
(29 reference statements)
1
8
0
Order By: Relevance
“…After successful IVC recanalization, TIPS was created for selected aBCS Type Ic patients. The details of TIPS procedures have been previously described . In brief, based on an indirect portovenogram, portal vein access was obtained between the IVC and the portal vein using Rosch‐Uchida system (Cook, Bloomington, IN, US).…”
Section: Methodssupporting
confidence: 92%
“…After successful IVC recanalization, TIPS was created for selected aBCS Type Ic patients. The details of TIPS procedures have been previously described . In brief, based on an indirect portovenogram, portal vein access was obtained between the IVC and the portal vein using Rosch‐Uchida system (Cook, Bloomington, IN, US).…”
Section: Methodssupporting
confidence: 92%
“…HVC‐BCS patients have undergone percutaneous recanalisation more frequently as compared to classical BCS patients . Several studies have shown good long‐term efficacy and survival‐benefit of this procedure (Table ) …”
Section: Radiological Interventionmentioning
confidence: 99%
“…Angioplasty has been extensively used in Asia with good long‐term outcomes (Table ) . Han et al published their experience in 168 Chinese BCS patients undergoing successful percutaneous angioplasty with median follow‐up of 30 months .…”
Section: Radiological Interventionmentioning
confidence: 99%
“…However, the use of TIPS in Asia is increasing, and available reports show similar positive results as in the West. [136][137][138][139][140] Recent data suggest that liver elastography measurements may be a good non-invasive test to evaluate the effectiveness of liver decompression. Currently this has been evaluated after invasive techniques such as balloon angioplasty (with or without stenting) in a small number of patients, showing a reduction of elastography measurement when the liver is adequately decompressed.…”
Section: Stepmentioning
confidence: 99%